Gráficos e Mutualismo: a trajetória da Associação Tipográfica Baiana (Salvador, final do século XIX e início do século XX) - Andrade, Humberto Santos de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In recent years, the historiography related to the history of workers and their movement regained momentum. In this context, mutual associations have merited special attention. The objective of this work is to try to understand and analyze the trajectory of Typographic Association Bahia, mutual benefit society founded in 1870 in the city of Salvador. This mutual, whose existence through the nineteenth and twentieth centuries, has left us an important legacy which represents an important portion of the history of Bahian workers, specifically field craft and typographer. Bring to a research academic discussion that removes the silence of the history of workers in Salvador, is to contribute to the understanding of issues related to the worlds of work in its relation to the formation of Brazilian society. The investigation of this form of association shows that the particularities of mutualism still have much to reveal to scholars of the subject, in addition to providing a better understanding of the forms of worker organization

Nos últimos anos, a historiografia relacionada à história dos trabalhadores e do seu movimento retomou fôlego. Nesse contexto, as associações mutualistas têm merecido atenção especial. O objetivo deste trabalho é tentar compreender e analisar a trajetória da Associação Tipográfica Baiana, sociedade mutualista fundada no ano de 1870, na cidade do Salvador. Essa mutual, cuja existência atravessa os séculos XIX e XX, deixou-nos um importante legado que representa parcela importante da história dos trabalhadores baianos, especificamente do campo e do ofício de tipógrafo. Trazer à discussão acadêmica uma pesquisa que retira do silêncio parte da história dos trabalhadores em Salvador é contribuir para o aprofundamento de questões relacionadas aos mundos do trabalho na sua relação com a formação da sociedade brasileira. A investigação dessa forma de associativismo demonstra que as particularidades do mutualismo ainda têm muito a revelar aos estudiosos da temática, além de proporcionar uma melhor compreensão das formas de organização dos trabalhadores
Keywords: Trabalho; História; Trabalhadores; Mutualismo; History; Salvador (BA)